Flipping The Classroom: How Reversing Teaching-Learning Process Can Improve Learner’s Comprehension in Learning Foreign Language - Wishnoebroto Wishnoebroto (Bina Nusantara University, 2014)
Flipping a classroom is not only recording classroom lesson into a video and bringing homework into the classroom. It is a whole new method with a lot better result compared to the traditional method. In western countries such as the US, flipping a classroom is already becoming a new method adopted by many different schools and universities. This paper tries to explore the possibility of flipping a classroom for learning foreign language at BINUS University by comparing it with the recent practices and findings in the western countries. After the analysis it can be concluded that this method can be applied at BINUS University but on several conditions such as the improvement of infrastructures, and the teacher’s awareness and understanding to optimize their understanding about flipped learning.